THE GENERAL CHINESE REMAINDER THEOREM - Iftene, Sorin; Chelaru, Florin (International Journal of Computing, 2014)
The Chinese remainder theorem deals with systems of modular equations. The classical variant requires the modules to be pairwise coprime. In this paper we discuss the general variant, which does not require this restriction on modules. We have selected and implemented several algorithms for the general Chinese remainder theorem. Moreover, we point out some interesting applications of this variant in secret sharing and threshold cryptography.